Improved Arterial Preservation Achieved by Combined Use of Indocyanine Green Angiography and Doppler Detector During Microsurgical Subinguinal Varicocelectomy. Issue 10 (25th November 2020) - Kurihara, Sota; Shibata, Yasuhiro; Arai, Seiji; Sekine, Yoshitaka; Miyazawa, Yoshiyuki; Koike, Hidekazu; Matsui, Hiroshi; Ito, Kazuto; Suzuki, Kazuhiro; Nakamura, Tetsuya
Abstract: Objectives: The microsurgical approach is considered the most reliable procedure in varicocelectomy. However, as there are difficulties in identifying the spermatic artery at the peripheral level, we had introduced intraoperative indocyanine green angiography (ICGA) for identification of arteries. In this study, we further investigated the usefulness of intraoperative ICGA in combination with an ordinary Doppler detector in microsurgical subinguinal varicocelectomy. Methods : A total of 140 men who underwent microsurgical subinguinal varicocelectomy at Gunma University Hospital were included. An operating microscope equipped with a near-infrared charge-coupled device was used for intraoperative ICGA. After exposing the vessels, arteries were identified using endoscopic vision only or with assistance of Doppler detector or ICGA, or of both. The number of preserved arteries was compared among the groups. Results : ICGA clearly visualized the internal spermatic arteries in all cases, allowing the surgeon to perform real-time identification and isolation of the spermatic artery intraoperatively. The use of ICGA or Doppler detector significantly increased the number of preserved arteries compared to the microscope-only operation from 1.11 to 1.75 ( p < 0.05) and 1.57 ( p < 0.05), respectively. The additional use of ICGA with Doppler detector further increased the number of preserved arteries to 2.41 ( p < 0.05). Conclusions : Intraoperative ICGA facilitated safe and quick microsurgical subinguinal varicocelectomy by enabling visualization of thin spermatic cord blood vessels. Improved preservation of thin arteries, which is essential for patients with infertility, can be achieved with the combined use of ICGA and ordinary Doppler detector.